2022
DOI: 10.3389/fbioe.2022.983988
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulated vaterite-calcite CaCO3 particles loaded with Mg2+ and Cu2+ ions with sustained release promoting osteogenesis and angiogenesis

Abstract: Bioactive cations, including calcium, copper and magnesium, have shown the potential to become the alternative to protein growth factor-based therapeutics for bone healing. Ion substitutions are less costly, more stable, and more effective at low concentrations. Although they have been shown to be effective in providing bone grafts with more biological functions, the precise control of ion release kinetics is still a challenge. Moreover, the synergistic effect of three or more metal ions on bone regeneration h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…To achieve the integration of collagen into the porous BBS, the adsorption of collagen on differently charged surfaces was investigated via a quartz crystal microbalance (QCM) and measurements of δ ‐potential in our previous studies. [ 36 ] Our findings indicated that collagen can be stably adsorbed on both negatively and positively charged surfaces because of its amphipathic nature. Therefore, the negatively charged BBS used in this study favored the adsorption of collagen under the specific process conditions with a net positive charge.…”
Section: Discussionmentioning
confidence: 89%
“…To achieve the integration of collagen into the porous BBS, the adsorption of collagen on differently charged surfaces was investigated via a quartz crystal microbalance (QCM) and measurements of δ ‐potential in our previous studies. [ 36 ] Our findings indicated that collagen can be stably adsorbed on both negatively and positively charged surfaces because of its amphipathic nature. Therefore, the negatively charged BBS used in this study favored the adsorption of collagen under the specific process conditions with a net positive charge.…”
Section: Discussionmentioning
confidence: 89%
“…In the context of biomaterials for craniofacial bone regeneration, the use of inorganic cations such as Ca 2+ , magnesium (Mg 2+ ), and silicon (Si 4+ ) has gained attention due to their influence on mechanical and biological properties crucial for bone regeneration [18,[65][66][67][68]. These cations do also play significant roles in neovascularization, which are crucial aspects of craniofacial bone regeneration [69][70][71][72]. Wang et al displayed a sustained release of Mg 2+ from the piezoelectric Whitlockite scaffold and promoted angiogenic differentiation of BMSCs in vitro.…”
Section: Cell Signaling and Angiogenic Growth Factorsmentioning
confidence: 99%
“…These studies remain controversial and have yet to be explored. Another promising direction is the synergistic effects of multiple bioactive cations on vascularization and bone defect repair, which is a much safer and simpler option [ 157 ].…”
Section: Applications Of Collagen In Bone Tissue Regeneration and Eng...mentioning
confidence: 99%